A systematic review exploring the variation in the compositional make‐up and phytochemical constituents of wheatgrass and pulse microgreens as a function of diverse growing condition - Arun Kumar; Narpinder Singh (eFood)
Abstract The wheatgrass and pulse microgreens have gained popularity for their concentrated phytochemical content. However, the variability in growth parameters and compositional constituents of wheatgrass and pulse microgreens is dependent on the prevailing environmental conditions. Nowadays, wheatgrass and pulse microgreens are used as culinary sources or incorporated into various food products and consumed by a large proportion of the global population. Therefore, it is necessary to review the impact of growth conditions to meet the increased demand. This will allow breeders to adjust their cultivation techniques according to consumer preferences for specific nutritional components. This systematic review seeks to provide an analysis of the available literature on the variation in growth and compositions of wheatgrass and pulse microgreens as the influence of diverse growing conditions. The growth of wheatgrass and pulse microgreens can be influenced by a range of growth conditions, such as variations in light intensity, temperature, nutrient availability, and cultivation techniques. The variation in growth and compositional components, in terms of proximate composition and certain constituents such as chlorophyll, antioxidants, minerals, phenolic compounds, and secondary metabolites, is discussed in relation to the changing cultivation parameters as published in recent studies. However, this review only covers the compositional make‐up of wheatgrass and pulse microgreens. There remains a need to summarize the compositional profiles of other microgreen species under various conditions. Ultimately, this review illuminates the promise of emerging superfoods and underscores how their growth and composition can vary depending on cultivation methods, ultimately impacting their capacity to promote health. In addition, there is a need to establish dose–response relationships to address various diseases. Therefore, additional research may be warranted.